Efficient angle-aware coverage control for large-scale 3D map reconstruction using drone networks - Muhammad Hanif; Takumi Shimizu; Lu Zhiyuan; Masaya Suenaga; Takeshi Hatanaka (SICE Journal of Control, Measurement, and System Integration)
This paper presents a novel angle-aware coverage control method to enhance monitoring efficiency for large-scale 3D map reconstruction using drone networks. The proposed method integrates a Voronoi-based coverage control as the nominal input into the quadratic programming problem required to solve in the original angle-aware coverage control. This approach provides a practical solution, ensuring diverse viewing angles to improve the quality of 3D map reconstruction and offers effective coverage of distant unobserved areas, particularly for large-scale area missions. We then implement the present method and validate its effectiveness through simulation on Robot Operating System as well as experiments conducted on a robotic testbed. The comparative analysis demonstrates the advantages of our proposed approach, resulting in increased monitoring efficiency for large-scale 3D map reconstruction.